Respuesta :
Answer:
Step-by-step explanation:
x^2-6=0
x^+6=0 ( add six to both sides)
x^2=6
x= the square root of 6 ( to get rid of the exponent you have to do the opposite....which is the square root)
x=2.44948974278
You may have to round if not given the exact number.
Answer:
[tex]x=\sqrt{6}[/tex] and [tex]x=-\sqrt{6}[/tex]
Step-by-step explanation:
We have the following quadratic equation
[tex]x^2-6=0[/tex]
To solve the equation add 6 to both sides of the equality
[tex]x^2-6+6=6[/tex]
[tex]x^2=6[/tex]
Now apply the square root function on both sides of the equation
[tex]\sqrt{x^2}=\sqrt{6}[/tex]
[tex]x=\±\sqrt{6}[/tex]
This means that the solutions are:
[tex]x=\sqrt{6}[/tex] and [tex]x=-\sqrt{6}[/tex]